A study of the effects of mobile media on L2 text processing: Beyond offline comprehension accuracy measures. (June 2022) - Hou, Jiarui; Lee, James F.; Doherty, Stephen
Abstract: Recent research on the processing effects of mobile media has incorporated offline research methods to demonstrate that reading on mobile media is as effective as reading on computers or paper in accuracy of text comprehension. The present study uses an eye-tracking methodology to compare the effects of reading on mobile media (mobile phone and tablet) and traditional media (paper and computer) on cognitive processing behaviours as well as on accuracy. Chinese L2 learners of English ( n = 156) read an English novel, The Elephant Man, in one of the four reading conditions (mobile phone: 41, tablet: 39, computer: 38, and paper: 38) while their eye movements were recorded. Between-condition comparisons showed that mobile-assisted reading performance was equally accurate, fast and efficient to process texts, and fast to respond to posttests. Statistically significantly shorter mean fixation duration of mobile-assisted than computer-assisted reading suggests slightly more efficiency in cognitive processing. The overall findings of the present study add to other strong evidence that mobile-assisted reading is effective in text processing. We discuss the implications of our results and provide directions for future research and insights into mobile-assisted language learning, including online learning, e.g., during the COVID-19 global pandemic. Highlights: Using eye-tracking to examine effects of mobile media on L2 text processing in comparison to traditional media. Examining text processing in three aspects: the end-result, the treatment text processing, and the posttest recall. Finding mobile-assisted reading performance equally accurate, fast and efficient to process, and fast to respond. Adding to other strong evidence of the effectiveness of mobile media in L2 text processing.